2021
DOI: 10.3390/ijerph18020599
|View full text |Cite
|
Sign up to set email alerts
|

Readiness and Willingness to Provide Immunization Services after Pilot Vaccination Training: A Survey among Community Pharmacists Trained and Not Trained in Immunization during the COVID-19 Pandemic in Poland

Abstract: Background: Immunization rates among the adult population in Poland are below desired targets, urging the need to expand this service in the community. During the COVID-19 pandemic, the ultimate goals for limiting the spread of the infection are vaccines against SARS-CoV-2. Pharmaceutical companies are in a race for the fastest possible way to deliver vaccines. Community pharmacists in Poland are recognised as an accessible yet underutilised group of medical professionals. Therefore, involving pharmacists in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 24 publications
3
67
1
Order By: Relevance
“…As of June 2021, Portugal, the Republic of Ireland, Switzerland, and the United Kingdom were the only countries among 13 in Europe having a legal framework for independent vaccinations by pharmacists [16]. Pharmacists providing vaccination services require confidence, knowledge, and skills [16], which can be addressed with appropriate training, increasing their self-reported readiness [21]. Only 15,617 of 1,152,000 delivered influenza vaccine doses (1.4%) were delivered in Swiss pharmacies in the season of 2017/2018 [22], whereas there were 271,962 of 7,211,350 delivered COVID-19 vaccine doses (3.8%; data until 23 June 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As of June 2021, Portugal, the Republic of Ireland, Switzerland, and the United Kingdom were the only countries among 13 in Europe having a legal framework for independent vaccinations by pharmacists [16]. Pharmacists providing vaccination services require confidence, knowledge, and skills [16], which can be addressed with appropriate training, increasing their self-reported readiness [21]. Only 15,617 of 1,152,000 delivered influenza vaccine doses (1.4%) were delivered in Swiss pharmacies in the season of 2017/2018 [22], whereas there were 271,962 of 7,211,350 delivered COVID-19 vaccine doses (3.8%; data until 23 June 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Polish community pharmacists who underwent additional immunization training showed a greater readiness to provide immunization services as compared with those who did not receive training. The most common barriers affecting Polish pharmacists' readiness were: providing vaccinations will require more work, not enough training courses, and pharmacy facilities are not adjusted to provide these services [18]. Acknowledging that readiness and willingness for vaccination are not mutually exclusive, our findings were comparable in showing that those who have completed additional training were more likely than unlikely to receive and recommend COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 60%
“…Overall, their findings highlight the crucial role patient cases play in training programs to help pharmacy and pharmacy staff identify eligible patients and improve vaccination rates. Finally, Merks et al [44] reported on the readiness and willingness of pharmacists in Poland to provide immunization services after completing the "Pharmacists Without Borders" educational workshops during the COVID-19 pandemic (February 2020-August 2020). Relevant to our work, the authors indicated that part of the apprehension pharmacists have toward providing vaccination services seem to stem from increased workload, not enough vaccination training courses and pharmacies not being adjusted to provide these types of services.…”
Section: Resultsmentioning
confidence: 99%